Language Assessment Literacy and Teachers' Professional Development: A Review of the Literature - Frank Giraldo (Universidad Nacional de Colombia, 2021)
In this literature review, I analyze the features and impacts of 14 programs which promoted teachers' language assessment literacy. I used content analysis to build a coding scheme with data-driven and concept-driven categories to synthesize and then analyze trends in the 14 research studies. Regarding core features, findings suggest that the programs were geared towards practical tasks in which teachers used theory critically. Also, the studies show that teachers expanded their conception of language assessment, became aware of how to design professional instruments, and considered wider constructs for assessment. Based on these findings, I include implications for the construct of language assessment literacy and recommendations for those who educate language teachers.